PRINTED MASS MEDIA TO IMPROVE READING SKILL OF JUNIOR HIGH SCHOOL DARUL FIKR ANDONG - Deni Sugiyarto (English Education Department Slamet Riyadi University Surakarta, 2018)
Reading is an important skill to help people learn from human knowledge and experience. Through reading, knowledge has greatly contributed to the growth of mankind. The aims of the study are as the following: (1) To identify whether the use of Printed Mass Media can improve the students’ reading skill at the Eight Grade of SMP DARUL FIKR Andong in 2017/2018 Academic Year., (2) To describe what happens when Printed Mass Media is applied at Eight Grade of SMP DARUL FIKR Andong in 2017/2018 Academic Year. The research was carried out at SMP Darul Fikr Andong. It was conducted from September until October 2017. The subject of the research was grade VIII-A students of SMP Darul Fikr Andong in 2017/2018 academic year. The research was carried out in 2 cycles of action. Each cycle consisted of: planning the action, implementing the action, observing, reflecting, and revising the plan. In collecting the data, the researcher used tests and non-tests. The tests consisted of pre-test and post-test. While non-tests were divided into three types: they were observation, interview and field note. To analyze the data, the researcher used qualitative and quantitative data. The qualitative data, he used Strauss and Glesser in Moleong analysis that consisted of data reduction, categorization, synthesis, stating action hypothesis.To analyze the quantitative data, the researcher used mean score and t -test formula. The results of the research show that printed mass media can improve students’ reading skill of the students at grade VIII-A of SMP DarulFikrAndong. The improvements can be seen from the students’ reading achievements. Themean score results was pre-test (49.1), post-test 1 (51. 1), and post-test 2 (74. 4). Then t-test value of cycle one is 0,33 and the t-test value of cycle two is 0,32. Based on the finding, the researcher concludes that PrintedMass Media is an appropriate media to improve students’ reading skill. Keywords :Printed Mass Media, Reading Skill,Classroom Action Research.